2016
DOI: 10.17161/iallt.v46i2.8560
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Online Translation on FL Writing Scores

Abstract: Online translation (OT) sites, which automatically convert text from one language to another, have been around for nearly 20 years. While foreign language students and teachers have long been aware of their existence, and debates about the accuracy and usefulness of OT are well known, surprisingly little research has been done to analyze the actual effects of online translator usage on student writing. The current study compares the scores of two composition tasks by third- and fourth-semester university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…In addition, while the language proficiency was consistent within a student's English text, the MT outputs sometimes contained inconsistencies. Particularly, as expressed by O'Neill (2014O'Neill ( , 2016, mismatches between the vocabulary and grammar levels, such as more advanced words in ill-formed sentences were found, which implied that the grammatical accuracy of MT is lower than its lexical accuracy. Ducar and Schocket (2018) argued that such irregularities in the students' L2 texts can be a telltale sign of the students' use of MT.…”
Section: Credibility Of Mt Outputsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, while the language proficiency was consistent within a student's English text, the MT outputs sometimes contained inconsistencies. Particularly, as expressed by O'Neill (2014O'Neill ( , 2016, mismatches between the vocabulary and grammar levels, such as more advanced words in ill-formed sentences were found, which implied that the grammatical accuracy of MT is lower than its lexical accuracy. Ducar and Schocket (2018) argued that such irregularities in the students' L2 texts can be a telltale sign of the students' use of MT.…”
Section: Credibility Of Mt Outputsmentioning
confidence: 96%
“…Previous studies have conducted preliminary research and presented tentative conclusions about the effectiveness of using MT in that, despite its inaccuracies, it remains useful for FL education (Briggs, 2018;Garcia, 2016;O'Neill, 2016;Sun, 2017). However, the quality of MT outputs has been rarely investigated in FL education; the majority of studies examined MT accuracy based on users' perceptions, and only a few empirical studies have been conducted that directly assess the accuracy of MT (Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From the L2 writing perspective, MT can support students' efforts to autonomously analyze and revise their written work (Baraniello et al, 2016). Studies have confirmed that using MT during the L2 writing process helps students to enhance the overall quality of their writing (Kol, Schcolnik & Spector-Cohen, 2018;O'Neill, 2016;Stapleton & Kin, 2019), focus more on content (Kim, 2011;O'Neill, 2016), and produce more lexically accurate and complex texts (Fredholm, 2019) with fewer orthographic errors (O'Brien, Simard & Goulet, 2018;Shadiev, Sun & Huang, 2019). Even in the relative infancy of MT technology, its outputs were found to benefit beginner writers in terms of improving the quality, quantity, and fluency of L2 writing (Garcia & Peña, 2011).…”
Section: Machine Translation As a Language Learning Toolmentioning
confidence: 99%
“…In fact, educational activities such as analyzing mistranslations, preediting, and post-editing were found to help develop meta-linguistic awareness by directing students' attention to the differences and similarities between their native language and their L2 (Abraham, 2009;Correa, 2014;Enkin & Mejías-Bikandi, 2016;Niño, 2009;Somers, 2003). O'Neill (2012O'Neill ( , 2016 found that such activities and training in the use of MT enable learners to write more accurately and receive higher subscores on L2 writing tasks (comprehensibility, spelling, content, and grammar) than those who did not. In addition to linguistic advantages, using MT as a supplementary tool has also been found to help lower student anxiety and increase confidence in language learning (Bahri & Mahadi, 2016;Jin, 2013;Niño, 2009).…”
Section: Limitations and Benefits Of Mtmentioning
confidence: 99%